Plasmacytoma‐like post‐transplant lymphoproliferative disorder seen in pediatric combined liver and intestinal transplant recipients. Issue 11 (27th June 2013) - Plant, Ashley S.; Venick, Robert S.; Farmer, Douglas G.; Upadhyay, Shivani; Said, Jonathan; Kempert, Pamela
Abstract Post‐transplant lymphoproliferative disease (PTLD) is a lymphoproliferative disorder secondary to chronic immunosuppression and is the most common malignancy in transplanted patients [Kamdar et al. Curr Opin Organ Transplant, 2011; 16:274–280]. Although PTLD usually presents as B or T cell lymphoma, plasmacytomas have been reported, mostly in the adult population. Six cases of pediatric plasmacytoma‐like PTLD have been reported, all of which were treated with vincristine, adriamycin, and dexamethasone (VAD), high dose dexamethasone alone, or dexamethasone + thalidomide [Tcheng et al. Pediatric Blood Cancer, 2006; 47:218–223; Perry et al. Blood, 2013; 8:1377–1383]. We present two cases of pediatric plasmacytoma‐like PTLD in combined liver and small bowel transplant patients both successfully treated with bortezomib and dexamethasone based on multiple myeloma protocols [Kyle and Rajkumar, Clin Lymphoma Myeloma, 2009; 9:278–288; Adams and Kaufmann, Cancer Invest, 2004; 22:304–311]. Pediatr Blood Cancer 2013;60:E137–E139. © 2013 Wiley Periodicals, Inc.